2022
DOI: 10.1158/0008-5472.can-21-1820
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting Circadian Rhythm via the PER1–HK2 Axis Reverses Trastuzumab Resistance in Gastric Cancer

Abstract: Trastuzumab is the only approved targeted drug for first-line treatment of human epidermal growth factor receptor 2 (HER2)-positive advanced gastric cancer (GC), but the high rate of primary resistance and rapid emergence of secondary resistance limit its clinical benefits. We found that trastuzumab-resistant (TR) GC cells exhibited high glycolytic activity, which was controlled by hexokinase 2 (HK2)-dependent glycolysis with a circadian pattern (higher at zeitgeber time 6, lower at zeitgeber time 18). Mechani… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…More recently, researchers have evidenced circadian evolutions in the expression and activity levels of the P-glycoprotein, a key protein in the efflux of multiple drugs by cancer cells [ 112 ]. Besides, it was shown that trastuzumab-resistant gastric cancer cells displayed PPARγ- and PER1-controlled circadian fluctuations in their glycolytic activity [ 113 ]. Interestingly, PER1 silencing alleviated the resistance to trastuzumab.…”
Section: Current Challenges and Perspectives: How To Define The Most ...mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, researchers have evidenced circadian evolutions in the expression and activity levels of the P-glycoprotein, a key protein in the efflux of multiple drugs by cancer cells [ 112 ]. Besides, it was shown that trastuzumab-resistant gastric cancer cells displayed PPARγ- and PER1-controlled circadian fluctuations in their glycolytic activity [ 113 ]. Interestingly, PER1 silencing alleviated the resistance to trastuzumab.…”
Section: Current Challenges and Perspectives: How To Define The Most ...mentioning
confidence: 99%
“…In that frame, some pioneer studies have already demonstrated that the anti-tumor efficacy of compounds could be highly variable depending on the time of administration. For example, the pharmacological administration of metformin at ZT6 in the gastric cancer model aforementioned significantly improved trastuzumab efficacy [ 113 ]. In another setting, namely a breast cancer xenograft model, the efficacy of erastin, an inhibitor of xCT cystine/glutamate transporter, was improved when administered during the light phase when compared to the dark phase [ 114 ].…”
Section: Current Challenges and Perspectives: How To Define The Most ...mentioning
confidence: 99%
“…PERIOD1 (PER1) is a clock gene involved in circadian rhythm regulation, DNA damage, cell cycle, cell proliferation, and metastasis. The abnormal expression of PER1 has been shown in various types of cancers, and both oncogenic and tumorsuppressive roles of PER1 have been revealed (11,60,61,(67)(68)(69)(70)(71)(72)(73)(74)(75)(76).…”
Section: Per1mentioning
confidence: 99%
“…Even if the recent combinatorial regimen of HER2 antibody plus PD-L1 antibody with chemotherapy showed favorable clinical results in unresectable and metastatic GC patients, the median duration of the response is just 1.1 months longer than the regimen without PD-L1 antibody [ 4 , 5 ]. On the other hand, acquired drug resistance is commonly developed after the treatments with chemotherapy and/or HER2 antibody in GC patients [ 6 , 7 ]. Thus, it is necessary and urgent to develop new strategies for advanced and metastatic GCs, especially design the new targeted drugs against novel molecules beyond HER2, which is only expressed in about one-fifth of GC patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%